Changes in food behavior during the first lockdown of COVID-19 pandemic: A multi-country study about changes in eating habits, motivations, and food-related behaviors. (July 2022) - Lamy, Elsa; Viegas, Claudia; Rocha, Ada; Raquel Lucas, Maria; Tavares, Sofia; Capela e Silva, Fernando; Guedes, David; Laureati, Monica; Zian, Zeineb; Salles Machado, Alessandra; Ellssel, Pierre; Freyer, Bernhard; et al.
Abstract: The COVID-19 pandemic resulted in severe, unprecedented changes affecting the world population. Restrictions in mobility, social distancing measures, and the persistent social alarm, during the first period of pandemic, resulted in dramatic lifestyle changes and affected physical and psychological wellbeing on a global scale. An international research team was constituted to develop a study involving different countries about eating motivations, dietary habits and behaviors related with food intake, acquisition, and preparation. This study presents results of an online survey, carried out during the first lockdown, in 2020, assessing food-related behavior and how people perceived them to change, comparatively to the period preceding the COVID-19 outbreak. A total of 3332 responses, collected from 16 countries, were considered for analysis [72.8% in Europe, 12.8% in Africa, 2.2% in North America (USA) and 12.2% in South America]. Results suggest that the main motivations perceived to drive food intake were familiarity and liking. Two clusters were identified, based on food intake frequency, which were classified as "healthier" and "unhealthier". The former was constituted by individuals with higher scholarity level, to whom intake was more motivated by health, natural concerns, and weight control, and less by liking, pleasure or affect regulation. The second cluster was constituted by individuals with a higher proportion of male and intake more influenced by affect-related motivations. During this period, a generalized lower concern with the convenience attributes of foods was noted (namely, choice of processed products and fast-food meals), alongside an increase in time and efforts dedicated to home cooking. Understanding the main changes and their underlying motivations in a time of unprecedented crisis is of major importance, as it provides the scientific support that allows one to anticipate the implications for the future of the global food and nutrition system and, consequently, to take the appropriate action.